Guidance for shared decision-making regarding orchiectomy in individuals with differences of sex development due to 17-β-hydroxysteroid dehydrogenase type 3 deficiency - Yu, Lissa X.; Johnson, Jodie; Pennesi, Christine M.; Ernst, Michelle M.; Strine, Andrew; Matheny Antommaria, Armand H.; Hopkin, Robert J.; Sandberg, David E.; Khorashad, Behzad; Mohnach, Lauren; Heider, Amer; Rutter, Meilan M. (Frontiers in Pediatrics, 2025)
17β-hydroxysteroid dehydrogenase type 3 deficiency is a 46,XY difference of sex development (DSD) that may present in childhood with inguinal testes or at puberty following virilization. We present four individuals, assigned female at birth, to highlight complexities and considerations surrounding orchiectomy. We reviewed the literature and created a “FACT sheet” to guide shared decision-making for patients, parents, and providers. “Ruth” presented at 16 months with inguinal herniae and underwent orchiectomy, based on parental preference. “Erica” presented at 13 years with voice deepening; she and her parents chose pubertal suppression and eventual orchiectomy. “Riley” presented at 18 months with inguinal herniae; after pubertal suppression and estrogen replacement, orchiectomy at age 13 years revealed germ cell neoplasia in situ. “Jordan” presented at birth with atypical genitalia and inguinal testes. Initially assigned female at birth, “Jordan's” sex was reassigned to male at 15 months; he subsequently underwent orchidopexy and expressed female gender identity at age 12 years. While early orchiectomy may eliminate pubertal androgens discordant with a female gender identity and remove malignancy risk, it necessitates pubertal induction and limits patient participation in decision-making. Fertility potential is unlikely; current fertility preservation protocols remain experimental for individuals with DSD. The stability of gender identity in this condition is difficult to predict. Postponing decision-making around testicular management allows the individual to meaningfully participate in the process and, if desired, undergo masculinizing puberty. Shared decision-making regarding testicular management requires consideration of predictions for gender identity stability, hormone replacement, testicular malignancy risk, and fertility potential.